Construction of eco-quality dual-suitable distribution areas for Dictamnus dasycarpus Turcz.: integrated analysis of MaxEnt model and multidimensional indicators - Jiang, Boqian; Wang, Dan; Ye, Qiuju; Luo, Jiayi; Jin, Bingqian; Yin, Haibo (Frontiers in Plant Science, 2025)
IntroductionDictamnus dasycarpus Turcz., a critical traditional medicinal plant in Northeast China, faces challenges of habitat degradation and unstable quality in cultivated populations.MethodsThis study systematically analyzed the key environmental drivers of its distribution and quality formation in Liaoning Province through an integrative framework combining the Maximum Entropy model (MaxEnt), High-Performance Liquid Chromatography (HPLC), and geodetector analysis.ResultsJuly precipitation (Prec7), temperature seasonality (Bio4), May solar radiation (Srad5), March maximum temperature (Tmax3), and March minimum temperature (Tmin3) were core variables influencing distribution patterns. The quality of cultivated populations was primarily regulated by February mean temperature (Tmean2) and May precipitation (Prec5), while that of wild populations were predominantly affected by January mean temperature (Tmean1). By overlaying ecological suitability zones, quality partitions, and existing planting areas, Chaoyang, Huludao, Jinzhou, Liaoyang, and Dandong were identified as ideal regions combining ecological adaptability and quality advantages.DiscussionThe study revealed that precipitation and temperature are key factors affecting both distribution and quality. Geodetector analysis confirmed significant interactions among environmental variables influencing both distribution and quality. The multi-model framework established in this study provides a scientific basis for precision cultivation zoning and wild resource conservation of medicinal plants. The identified high-quality planting regions can promote the sustainable development of the D. dasycarpus industry, and the methodological approach provides a reference for similar studies.